2010
DOI: 10.1371/journal.pone.0009692
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation as a Biomarker for Cardiovascular Disease Risk

Abstract: BackgroundElevated serum homocysteine is associated with an increased risk of cardiovascular disease (CVD). This may reflect a reduced systemic remethylation capacity, which would be expected to cause decreased genomic DNA methylation in peripheral blood leukocytes (PBL).Methodology/Principal FindingsWe examined the association between prevalence of CVD (myocardial infarction, stroke) and its predisposing conditions (hypertension, diabetes) and PBL global genomic DNA methylation as represented by ALU and Satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
212
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(223 citation statements)
references
References 26 publications
9
212
0
2
Order By: Relevance
“…In this regard, epigenetic factors are emerging as an area of great interest on account of being modifiable through extracellular stresses, including air pollution, in contrast to genetic factors. Subsequently, many studies have assessed the effect of air pollution on global genomic DNA methylation (Alu, Satellite 2, and LINE‐1 repetitive elements) and gene‐specific DNA methylation (eg, ALOX15 , AMOTL2 , ARHGAP24 , IGF2 , and PECAM ), mainly using blood cells as a surrogate marker 18, 19, 20, 21, 22. For the first time, we have demonstrated a potential role for mtDNA methylation in the association between PM 2.5 exposure and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, epigenetic factors are emerging as an area of great interest on account of being modifiable through extracellular stresses, including air pollution, in contrast to genetic factors. Subsequently, many studies have assessed the effect of air pollution on global genomic DNA methylation (Alu, Satellite 2, and LINE‐1 repetitive elements) and gene‐specific DNA methylation (eg, ALOX15 , AMOTL2 , ARHGAP24 , IGF2 , and PECAM ), mainly using blood cells as a surrogate marker 18, 19, 20, 21, 22. For the first time, we have demonstrated a potential role for mtDNA methylation in the association between PM 2.5 exposure and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Previous studies have suggested that DNA methylation in these types of sequences may play a role in complex diseases other than cancer, such as cardiovascular diseases and diabetes. 9,10,20 It is well known that DNA methylation is a dynamic process and it is affected by environmental factors, both from development in uterus (intrauterine development) and in adult life. Several of these environmental exposures are associated with the risk of complex diseases.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although most epigenetic studies have been focused on cancer, 7,8 , previous studies have suggested that DNA methylation in these LINE-1 elements may play a role in other complex human diseases, such as cardiovascular disease or diabetes. [9][10][11][12] However, there are still many unresolved issues about the role of epigenetic changes in the study of complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a loss of genomic DNA methylation has been described to occur in several types of tissue during aging and age-related diseases (Fraga et al 2007;Bollati et al 2009;Kim et al 2010;Choi et al 2009;Moore et al 2008). In addition, global genomic hypomethylation of leukocyte DNA has been reported to be an independent risk factor for cancer, atherosclerosis, and cardiovascular disease (Fraga et al 2007;Kim et al 2010;Choi et al 2009;Moore et al 2008). DNA hypomethylation occurs mostly in transposable DNA repetitive elements, including the Alu and LINE-1 sequences, which play a crucial role in gene regulation and genomic stability.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of global DNA methylation and promoter hypermethylation of several specific genes occur during aging. Epigenetics plays an important role in cellular senescence, human tumorigenesis, and several agerelated diseases (Fraga et al 2007;Bollati et al 2009;Kim et al 2010;Choi et al 2009;Moore et al 2008;Rakyan et al 2010;Chambers et al 2007). Indeed, epigenomic alterations are now increasingly recognized as part of aging and its associated pathologic phenotype (Petronis 2010;Bellizzi et al 2011).…”
Section: Introductionmentioning
confidence: 99%